2004
DOI: 10.1007/s00122-003-1555-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal location of genes for novel glutenin subunits and gliadins in wild emmer wheat (Triticum turgidum L. var. dicoccoides)

Abstract: The glutenin and gliadin proteins of wild emmer wheat, Triticum turgidum L. var. dicoccoides, have potential for improvement of durum wheat ( T. turgidum L. var. durum) quality. The objective of this study was to determine the chromosomes controlling the high molecular weight (HMW) glutenin subunits and gliadin proteins present in three T. turgidum var. dicoccoides accessions (Israel-A, PI-481521, and PI-478742), which were used as chromosome donors in Langdon durum- T. turgidum var. dicoccoides (LDN-DIC) chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The band having slightly faster mobility derived from chromosome 1A because it was absent in LDN 1D(1A) but present in LDN 1D(1B) substitution (Figure 4, lanes 10 and 11). Similarly, the band with slightly slower Joppa et al (1983) and Xu et al (2004), except that the chromosomal locations for bands 22 were determined in this study. (Figure 4, lanes 1, 9, 11) were the same as bands 19, 22 and 50 in Renville (Figure 4, lanes 7 and 15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band having slightly faster mobility derived from chromosome 1A because it was absent in LDN 1D(1A) but present in LDN 1D(1B) substitution (Figure 4, lanes 10 and 11). Similarly, the band with slightly slower Joppa et al (1983) and Xu et al (2004), except that the chromosomal locations for bands 22 were determined in this study. (Figure 4, lanes 1, 9, 11) were the same as bands 19, 22 and 50 in Renville (Figure 4, lanes 7 and 15).…”
Section: Resultsmentioning
confidence: 99%
“…The chromosomal locations of most gliadin proteins in LDN were determined by Joppa et al (1983) and Xu et al (2004). The chromosomal location of band 22 was not previously determined.…”
Section: Resultsmentioning
confidence: 99%
“…Gene transfers from species belonging to the primary gene pool of Triticum into common wheat can be achieved by direct hybridization, homologous recombination, backcrossing and selection (McFadden, 1930). Accordingly, T. dicoccoides is a valuable genetic resource possessing genes for potentially major impact on future wheat breeding programs in regard to quality Xu et al, 2004) and pathogen resistance (Gerechter-Amitai & Stubbs, 1970;Moseman et al, 1985;Nevo et al, 1985;Hsam & Zeller, 2002). Wild emmer has been reported to be highly resistant to powdery mildew (Gerechter-Amitai & van Silfhout, 1984;Moseman et al, 1984).…”
Section: Introductionmentioning
confidence: 97%
“…Two sets of LDN-T. dicoccoides disomic substitution lines were recently developed using two resistant T. dicoccoides accessions as chromosome donors (Joppa, unpublished;Xu et al, 2004). Evaluation of these substitution lines for reaction to FHB in the greenhouse indicated that chromosomes 5B and 7A in the T. dicoccoides accessions conferred resistance to FHB (Stack et al, 2003b).…”
Section: Wheat-alien Species Derivatives Resistant To Fhbmentioning
confidence: 97%